2023
DOI: 10.3389/fpsyg.2023.1293783
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pre-task music on exercise performance and associated psycho-physiological responses: a systematic review with multilevel meta-analysis of controlled studies

Slaheddine Delleli,
Ibrahim Ouergui,
Christopher Garrett Ballmann
et al.

Abstract: This systematic review summarized the studies that examined the pre-task music effects on performance aspects and quantitatively analyzed their outcomes. A systematic search for controlled studies investigating the acute effects of pre-task music on physical performance, cognitive aspects and associated psycho-physiological responses was performed through Scopus, PubMed, Web of Science and Cochrane Library databases up to 17 May 2023, with thirty studies fulfilled the inclusion criteria. Data was analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 91 publications
0
0
0
Order By: Relevance
“…However, CAF 13,14 and warm-up music 63 ergogenic potentials have been established through the menstrual cycle. Because the most common symptoms experienced during the menstrual cycle are mood changes/anxiety, and tiredness/fatigue 64 , such results may be reasonable since CAF and music commonly serve to regulate affective and neuromuscular responses 9,26,60 Although the present study provides unique and interesting findings to female athletes, some limitations should be declared. In fact, no neurological or hormonal measurements were conducted to explain the mechanisms under the synergetic effect of CAF and warm-up music.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…However, CAF 13,14 and warm-up music 63 ergogenic potentials have been established through the menstrual cycle. Because the most common symptoms experienced during the menstrual cycle are mood changes/anxiety, and tiredness/fatigue 64 , such results may be reasonable since CAF and music commonly serve to regulate affective and neuromuscular responses 9,26,60 Although the present study provides unique and interesting findings to female athletes, some limitations should be declared. In fact, no neurological or hormonal measurements were conducted to explain the mechanisms under the synergetic effect of CAF and warm-up music.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that the ergogenic potential of CAF on taekwondo specific performance is dependent on competition level, with greater benefits in elite than sub-elite athletes 45 . For warm-up music, recent meta-analysis revealed that this stimulus present greater effects in highly trained subjects than less trained ones regarding psychological responses and the reverse for physical performances 26 . Since participants in the present study are elite athletes, their greater responses to the CAF + M condition may be related to complementary actions by CAF and music at the central and peripheral levels 23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations